2023
DOI: 10.1519/jsc.0000000000004512
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Exercise Versus Heavy Resistance Exercise Protocols: Which Resistance Priming Is More Effective for Improving Neuromuscular Performance on the Following Day?

Abstract: Nishioka, T and Okada, J. Ballistic exercise versus heavy resistance exercise protocols: which resistance priming is more effective for improving neuromuscular performance on the following day? J Strength Cond Res 37(10): 1939–1946, 2023—This study aimed to determine whether ballistic exercise priming (BEP) or heavy resistance priming (HRP) is more effective for improving ballistic performance after 24 hours. Ten resistance-trained men performed BEP and HRP conditions 72–144 hours apart in a randomized and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Findings from previous research have demonstrated that placebo effects have a biological basis and can strongly influence performance measures. 49 Considering the equivocal results of priming studies, 57,10,11,1517,22,24,28,29 it may be that an exercise stimulus produces a positive or negative performance outcome simply because the athlete believes one or the other to be true. Accordingly, practitioners seemed willing to utilise priming strategies so long as their athletes perceived it to influence performance positively, as Walter remarked:A lot of it from our perspective is probably more subjective.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings from previous research have demonstrated that placebo effects have a biological basis and can strongly influence performance measures. 49 Considering the equivocal results of priming studies, 57,10,11,1517,22,24,28,29 it may be that an exercise stimulus produces a positive or negative performance outcome simply because the athlete believes one or the other to be true. Accordingly, practitioners seemed willing to utilise priming strategies so long as their athletes perceived it to influence performance positively, as Walter remarked:A lot of it from our perspective is probably more subjective.…”
Section: Resultsmentioning
confidence: 99%
“…1,4 However, recent findings suggest that performance may be improved within 1–48 hours following these sessions providing the amount of work completed is relatively low. 512 Termed ‘priming exercise’, studies have revealed improvements in different forms of strength expression (e.g. heavy maximal 1315 and fast 57,912,16 dynamic strength) and maximal running ability 13,17,18 within this time frame following low-volume exercise stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heavy-resistance-training (HRT) elicits a plethora of adaptations on a structural and neural level and HRT programs utilize relatively high load/high force (>70% one repetition maximum (1-RM)) and thus lower velocity, relatively few repetitions (4-8 repetitions), and isoinertial exercises like the bench press or squat [7]. However, although many specialists recommend the use in soccer players of HRT, resistive exercise with high loads (range 70-90% 1-RM), they also recommend high volumes, meaning sets of repetitions ending at or close to volitional fatigue [8,9].…”
Section: Introductionmentioning
confidence: 99%